Mrs. Miracle [videorecording (DVD)] - Roberts, Doris, 1925-2016; Karpluk, Erin, 1978-; Van der Beek, James, 1977-; Macomber, Debbie (Sony Pictures Home Entertainment, 2010)
When her acting career does not take off, but her sister does with her fiance, Reba returns home to become a preschool teacher, and director of the Christmas pageant. After his wife dies, widower Seth Webster moves to town with his rambunctious twin boys. Mrs. Merkle, who is dubbed 'Mrs. Miracle' by the boys, is hired as a nanny and soon has the boys behaving nicely. It isn't long before Mrs. Miracle is sowing the seeds of love for Reba and Seth too. Was Mrs. Miracle really sent from up above?